Cross-linking structure-induced strong blue emissive gold nanoclusters for intracellular sensing. Issue 8 (14th March 2019) - Yang, Lina; Lou, Xuefen; Yu, Fanfan; Liu, Honglin
Abstract : Fluorescent gold nanoclusters (Au NCs) are new emerging fluorescent nanomaterials with broad application prospects but limited by the complicated preparation, low quantum yield (QY) and poor biological applications. Abstract : Fluorescent gold nanoclusters (Au NCs) are new emerging fluorescent nanomaterials with broad application prospects but limited by the complicated preparation, low quantum yield (QY) and poor biological applications. Here we develop a one pot etching approach for synthesizing fluorescent Au NCs by using the common citrate-capped gold nanoparticles (Au NPs) as the precursor and the poly(amidoamine) (PAMAM) dendrimer as the etching and templating agent. The synthesis conditions are optimized and products are characterized in detail. The results confirm that we have successfully synthesized PAMAM-templated Au NCs (Au-PAMAM NCs) with strong blue emission at 453 nm and a high fluorescence QY of 18%. The optical properties are remarkably superior to that of most other reported fluorescent Au NCs since the formed specific cross-linking structures of Au-PAMAM NCs rigidify the surface Au(i )-ligands and enhance the inner aurophilic interactions. Interestingly, Au-PAMAM NCs display a sensitive and selective fluorescence response toward temperature and Cr2 O7 2− ions, respectively. Quantitative analysis reveals the excellent capacity to distinguish temperature in the range of 15 °C–80 °C and to sense Cr2 O7 2− in a linear range of 0–55 μM with a detection limit of 1.9 μM. Experiments evidence that there is no interference when sensing each of these targets, making Au-PAMAM NCs potential fluorescent probes for these two targets. By means of the small size, excellent water solubility, negligible cytotoxicity, and great cell penetration ability, Au-PAMAM NCs are successfully applied to monitor the dynamic change of temperature and Cr2 O7 2− ions in living cells. This study paves the way for synthesizing high emission and highly biocompatible Au NCs with promising potential in biosensing and imaging in the future.